The impact of ESG environmental performance on corporate performance: evidence from China - Wu, Di; Zhu, Qingxin (Frontiers in Sustainability, 2025)
Against the backdrop of global sustainable development, how to translate environmental performance under the ESG framework into tangible corporate outcomes remains a pressing issue that warrants in-depth investigation. Drawing on data from China’s A-share listed firms from 2006 to 2022, this study empirically examines the impact of ESG environmental performance on corporate performance. The results reveal that ESG environmental performance significantly enhances corporate performance. This finding remains robust after addressing potential endogeneity by employing analyst attention as an instrumental variable and treating the implementation of the Environmental Protection Law as a quasi-natural experiment. The mechanism analysis indicates that green innovation serves as a crucial channel through which ESG environmental performance promotes corporate performance. Further, the moderating analysis shows that firms with stronger market competitiveness amplify the positive effect of ESG environmental performance on corporate performance. This amplification arises from the dual mechanism of strengthening the contribution of green innovation to firm performance while simultaneously weakening the driving effect of ESG environmental performance on green innovation. The heterogeneity analysis demonstrates that the positive impact of ESG environmental performance on corporate performance is more pronounced among non-state-owned enterprises, firms with executives holding green backgrounds, companies without environmental penalties, and those operating in non-high-tech and non-high-pollution industries. Overall, this study provides theoretical support for corporate green transformation and offers valuable policy implications for optimizing sustainable development strategies.